2023
DOI: 10.3389/fimmu.2023.1121273
|View full text |Cite
|
Sign up to set email alerts
|

The causality between intestinal flora and allergic diseases: Insights from a bi-directional two-sample Mendelian randomization analysis

Abstract: BackgroundGrowing evidence shows a significant association between intestinal flora and allergic diseases, specifically atopic dermatitis (AD), allergic rhinitis (AR), and allergic asthma (AA). However, the causality has not yet been clarified.ObjectiveWe conducted a bidirectional two-sample Mendelian randomization (TSMR) analysis to study the causal relationships between intestinal flora classification and AD, AR, or AA.Materials and methodsWe obtained summary data of intestinal flora, AD, AR, and AA from a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 58 publications
(76 reference statements)
0
33
0
1
Order By: Relevance
“…Previous studies have shown a causal relationship between gut microbiota and allergic diseases, as gut microbial dysbiosis can lead to abnormal immune reactions and promote the development of AR 5,6 . Prebiotics can regulate gut dysbiosis, 23 providing a new therapeutic approach for indirectly affecting the progression of AR by modulating the gut microenvironment through prebiotic intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown a causal relationship between gut microbiota and allergic diseases, as gut microbial dysbiosis can lead to abnormal immune reactions and promote the development of AR 5,6 . Prebiotics can regulate gut dysbiosis, 23 providing a new therapeutic approach for indirectly affecting the progression of AR by modulating the gut microenvironment through prebiotic intake.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics Previous studies have shown a causal relationship between gut microbiota and allergic diseases, as gut microbial dysbiosis can lead to abnormal immune reactions and promote the development of AR. 5,6 Prebiotics can regulate gut dysbiosis, 23 providing a new therapeutic approach for indirectly affecting the progression of AR by modulating the gut microenvironment through prebiotic intake. The advantage of prebiotics lies in their selective fermentation by bifidobacteria or lactobacilli, dependent on stimulating the host's own bifidobacteria or lactobacilli populations.…”
Section: No Prebiotics Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) A linkage disequilibrium (LD) analysis (R2 < 0.001, clumping distance = 10,000kb) was performed to satisfy the MR hypothesis. It is important to avoid weak instrument bias when inferring causal relationships, we used the formula F = β 2 exposure/SE 2 exposure to calculate the intensity of IVs [19][20][21] and excluded IVs with F < 10 (23). GWAS summary statistics for skin diseases were extracted from the FinnGen research project (https://r5.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Daher stellt ein gesunder Darm ein Schlüsselelement zu mehr Gesundheit und Wohlbefinden im Allgemeinen dar. So haben Aufbaustudien gezeigt, dass Menschen mit einer gesunden Darmflora deutlich weniger anfällig für Allergien und Unverträglichkeiten sind [ 1 , 2 ]. Das ist deshalb so, weil die nützlichen Darmbakterien die vorderste Front unseres Körperabwehrsystems darstellen [ 3 ].…”
Section: Kurz Gefasstunclassified